In vitro antiplasmodial, antileishmanial and antitrypanosomal activities of selected medicinal plants used in the traditional Arabian Peninsular region - Al-Musayeib, Nawal M (BioMed Central, 2012)
BACKGROUND: Worldwide particularly in developing countries, a large proportion of the population is at risk for tropical parasitic diseases. Several medicinal plants are still used traditionally against protozoal infections in Yemen and Saudi Arabia. Thus the present study investigated the in vitro antiprotozoal activity of twenty-five plants collected from the Arabian Peninsula. METHODS: Plant materials were extracted with methanol and screened in vitro against erythrocytic schizonts of Plasmodium falciparum, intracellular amastigotes of Leishmania infantum and Trypanosoma cruzi and free trypomastigotes of T. brucei. Cytotoxic activity was determined against MRC-5 cells to assess selectivity. The criterion for activity was an IC(50) < 10 μg/ml (<5 μg/ml for T. brucei) and selectivity index of >4. RESULTS: Antiplasmodial activity was found in the extracts of Chrozophora oblongifolia, Ficus ingens, Lavandula dentata and Plectranthus barbatus. Amastigotes of T. cruzi were affected by Grewia erythraea, L. dentata, Tagetes minuta and Vernonia leopoldii. Activity against T. brucei was obtained in G. erythraea, L. dentata, P. barbatus and T. minuta. No relevant activity was found against L. infantum. High levels of cytotoxicity (MRC-5 IC(50) < 10 μg/ml) and hence non-specific activities were noted in Cupressus sempervirens, Kanahia laniflora and Kniphofia sumarae. CONCLUSION: The results endorse that medicinal plants can be promising sources of natural products with antiprotozoal activity potential. The results support to some extent the traditional uses of some plants for the treatment of parasitic protozoal diseases.